Assessing multi-level congruence in voting in comparative perspective: Introducing the municipal level. Issue 1 (2nd January 2021) - Bolgherini, Silvia; Grimaldi, Selena; Paparo, Aldo
ABSTRACT: This article widens the theoretical debate on congruence in voting by including the municipal level on top of the consolidated national-regional comparisons. The concept of multi-level congruence (MLC) is introduced and an original dataset is computed in order to investigate two distinct territorial-level comparisons in Italy and Spain: the national-municipal and the regional-municipal. By building on several strands of literature, the article tests different predictors of congruence. Our findings show that local elections are more likely to be impacted by national (and, to a smaller extent regional) politics in central, large municipalities; while local politics is more likely to prevail in peripheric, small municipalities. Moreover, municipal elections are second-order with respect to the national-level at least when election timing is taken into account. Furthermore, historical voting patterns also play a role in explaining the incongruence between local and national elections. Finally, national party-system reshuffle (slightly) affects congruence only for the regional-municipal comparison – and surprisingly not for the national-municipal one.